THE TITANIC - Charman, Katrina (New York : Little, Brown and Company, 2018)
"A stowaway dog and the captain's cat forge an unlikely friendship as they race to protect three kittens, help their humans, and survive the sinking of the Titanic."
Ages 9-13.
Keywords: Children's stories, English; English fiction; Titanic (Steamship) -- Fiction